Natural English. Reading Writing Skills. Pre-intermediate: Resource Book - Clementson T. Theresa (New York, Oxford University Press, 2009)
The Reading and writing resource books series is a flexible photocopiable resource for teachers. At each level, you can use the material alongside the natural English student's book as extra topic-related skills work or on its own as a dip-in resource. The lessons are based around topical, authentic texts and practise a range of reading and writing skills ideal for students who are on general English courses, doing academic studies, or working.